Political Discourse Analysis: A Critical Analysis of Donald Trump’s Political Speeches - El Bakri, Jawad (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2025)
This research paper explores political discourse analysis in relation to language use, focusing on how political actors employ communication to legitimize policies, influence audiences, and shape perceptions of social and political realities. It examines the historical roots of this relationship and analyzes tools for studying political speech, with a particular focus on the intersection of discourse and manipulation. The paper includes a practical analysis of speeches by former U.S. President Donald Trump, especially regarding his slogan “Make America Great Again,” exploring themes like immigration, ISIS, nuclear agreements, and Russian interference in the 2016 elections. The study also tests the hypothesis that Trump frequently contradicts himself on these issues.